First-principles predictions of anisotropies in elasticity and sound velocities of CsCl-type refractory intermetallics: TiTM, ZrTM and HfTM (TM = Fe, Ru, Os). Issue 21 (2nd November 2019) - Bao, Weizong; Liu, Dan; Duan, Yonghua; Peng, Mingjun
ABSTRACT: Structural properties, elastic properties, sound velocities and Debye temperatures of CsCl-type refractory TiTM, ZrTM and HfTM (TM = Fe, Ru, Os) intermetallics were investigated using first-principles calculations. The calculated equilibrium lattice parameters are coincided with the reported experimental and theoretical data. Based on single-crystal elastic constants, polycrystalline elastic moduli, Poisson's ratios, sound velocities and Debye temperatures were evaluated. Anisotropies in elastic moduli of these CsCl-type intermetallics were discussed by elastic anisotropy indexes, three-dimensional surface constructions and their projections, and directional elastic modulus. The results showed that ZrFe has the highest elastic anisotropy and ZrOs presents the lowest one. Finally, sound velocities, Debye temperatures and their anisotropies were also calculated and discussed.